Assessment of molecular DNA damage and oxidative stress in mice intestinal tissues following 50% watermelon juice supplementation / Mohamad Shafiq Mat Salleh - Mat Salleh, Mohamad Shafiq (2015)
Ionizing radiation (lR) has been extensively used as therapy and diagnostic modality to detect abnormalities inside human body, but elicit both beneficial and deleterious role. Interaction between and IR and cells can leads to production of free radicals thus causing oxidative stress. By using animal model system, our aim is to assess molecular DNA damage and oxidative stress in mice intestinal tissue following 50% watermelon juice supplementation for 14 days. Twenty four (24) of6 weeks old male ICR mice were randomly selected into four groups, which are negative control group (-ve), antioxidant group (Aox), radiation group (Rx) and treatment group (Tx). Cx were treated with normal diet and filtered tap water; Aox were treated with normal diet and 50% watermelon juice; Rx were treated with normal diet, filtered tap water and irradiated with 100 IlGy x-ray; Tx were treated with normal diet, 50% watermelon juice and irradiated with 100 IlGy x-ray. After 14 days, the levels of superoxide dismutase (SOD), reduced glutathione (GSH) and malondialdehyde (MDA) in intestinal tissues were elucidated by using biochemical analysis and comet assay for demonstration of oxidative stress and DNA damage. Comet assay revealed significant reduction of DNA damage in 50% watermelon juice supplemented group compared to radiation group (p=0.00) and pair-wise relationship between Aox and Cx showed significant difference with p=0.003. Between Rx and Cx, the DNA damage were statistically significant at p=O.OO. GSH levels for Rx and Tx yield significant reduction compared to Cx with p=O.OO and p=O.OO respectively. Significant reduction of DNA damage confirmed ameliorative effect of 50% watermelon juice while reduction of GSH level suggested a high consumption of natural antioxidant to combat oxidative stress prior to IR exposure. The outcomes highlighted that supplementation of 50% watermelon juice for 14 days have a radioprotective properties against DNA damage induced by IR.